The Management of Tahsin and Tahfidz Al-Qur'an Learning for Non-Resident Students - Devi Sartika; Elce Purwandari; Helsi Arista; Deti Murni; Idi Warsah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Tahsin is a learning activity to improve the reading of the Qur'an while tahfidz is an effort to memorize verses in the Qur'an. This study aims to determine the management of learning tahsin and tahfidz Al-Qur'an for non-mukim students at Islamic Junior High School Ulul Albab Lubuklinggau. The method used in this research is the qualitative method. Data collection techniques in this study were observation, interviews, and documentation. The results of this study indicate that: (1) The planning of the tahsin learning system at the Ulul Albab Islamic Middle School is carried out by assessing the needs or identifying problems, formulating goals and objectives, formulating policies, implementing policies and assessing plans (2) The implementation of tahsin learning takes into account several components (a) the aim is to get used to reading the Qur'an correctly and fluently, (b) the material emphasized is tajwid, majhrijur letters that are continued al-syakal, gharib. (c) the media used is visual media, print media (d) the method used is talaqqi and musyafahah with classical reading, listening and lecture techniques, (e) evaluation is carried out at the end of each meeting, semester, and yearly, (3). The result is increased knowledge, skills, and attitudes.